Determinant of Interest in Paying Zakat with Age as a Moderating Variable (Study on Minang Society) - Harmaini; Basri, Yuswar Zainul; Arafah, Willy (APTISI Transactions on Management (ATM), 2023)
This study wants to test whether there is an influence between Zakat Knowledge, Religiosity, Culture, Subjective Norms, and Income on Muzaki Minang's zakat interest in paying zakat, with age as a moderating variable. The purpose of this study will be to analyze and describe the effect of Muzaki Minang's interest in tithing by using a theoretical model. The data collection technique used a questionnaire and sampling was done by purposive sampling with a total of 320 respondents. The population in this study is the Muzaki Minang population who live in West Sumatra and outside West Sumatra. The data analysis technique used is descriptive statistical analysis. The results of this study are the knowledge of zakat and culture variables do not affect Muzaki's interest in zakat. While the interest in paying zakat which has a significant and positive effect is religiosity, subjective norms, and income. There is a moderate relationship between income and age with interest in paying zakat. The dominant age factor is early adulthood (20-40 years) compared to old age (>40 years). The findings of this study are helpful input for the leaders of the indigenous people of West Sumatra in strengthening the understanding of the younger generation about Minang customs. With the increasing understanding of adat for the Minang community, they are interested in paying zakat themselves and using zakat as a tool to improve people's welfare.